Redistribution policy and inequality reduction in OECD countries: What has changed in two decades? - Herwig Immervoll; Linda Richardson (Institute for the Study of Labor (IZA), 2011)
We use a range of data sources to assess if, and to what extent, government redistribution policies have slowed or accelerated the trend towards greater income disparities in the past 20-25 years. In most countries, inequality among non-elderly households has widened during most phases of the economic cycle and any episodes of narrowing income differentials have usually not lasted long enough to close the gap between high and low incomes that had opened up previously. With progressive redistribution systems in place, greater inequality automatically leads to more redistribution, even if no policy action is taken. We find that, in the context of rising market-income inequality, tax-benefit systems have indeed become more redistributive since the 1980s but that this did not stop income inequality from rising: market-income inequality grew by twice as much as redistribution. Between the mid-1990s and the mid-2000s, the redistributive strength of tax-benefit systems then weakened in many countries. While growing market-income disparities were the main driver of inequality trends between the mid-1980s and mid-1990s, reduced redistribution was often the main reason why inequality rose in the ten years that followed. Benefits had a much stronger impact on inequality than social contributions or taxes, despite the much bigger aggregate size of direct taxes. As a result, redistribution policies were often less successful at counteracting growing income gaps in the upper parts of the income distribution.
urn:nbn:de:101:1-201110263744
Keywords: D31; H22; H55; C81; 330; income inequality; redistribution; working age; OECD; Einkommensumverteilung; Verteilungspolitik; Wirkungsanalyse; Verteilungswirkung; Einkommensverteilung; OECD-Staaten